PERBEDAAN HASIL BELAJAR DARI MODEL PROJECT BASED LEARNING DAN MODEL KONVENSIONAL (CERAMAH) PADA MATERI EKOSISTEM SMP NEGERI 5 KUPANG - Nofri Wake Lulu; Mario J Santrum; Andam Suriaty Ardan; Moses Kopong Tokan (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This research aims to determine the influence of the project based learning model to improve student learning outcomes in class VII ecosystem material at SMP Negeri 5 Kupa This study aims to determine whether there are differences between the project-based learning model and the conventional model (lecture) regarding the topic of ecosystems for Grade VII students at SMP Negeri 5 Kupang. ng. This type of research is quasi-experimental which refers to a quantitative approach with data collection techniques through tests, observation and documentation. The sampling technique is random sampling. The results of the research show that there is a difference in the average pretest score, namely in the experimental class 46,16 and control 34.10, while in the posttest the experimental class average is 80,13 and the control class is 61.80, supported by the results of the hypothesis test, namely the t-test, which found a result of 0.000, which is smaller than 0.05, so Ho is rejected and H is accepted, in other words, there is the influence of the project based learning model to improve student learning outcomes in ecosystem material. Kupang 5 Public Middle School. The conclusion of this research is that there is an influence of the project based learning learning model to improve student learning outcomes in class VII ecosystem material at SMP Negeri 5 Kupang